Screening for cervical cancer in Africa: A proposal of a different combination of VIA test and cervical smear in Uganda. Issue 1 (16th September 2020) - Corrado, Giacomo; Mazzara, Calogero; Certelli, Camilla; Nsubuga, John B.; Zanetto, Francesca; Schurfeld, Karin; Dell'Antonio, Giacomo; Orti, Carlino D.; Savarese, Antonella; Andriani, Maria T.
Abstract: Objective: To evaluate the efficacy of visual inspection with acetic acid (VIA) screening combined with a cervical smear in Uganda. Methods: Nine screening campaigns were held in Uganda between January 2011 and October 2019. In the last three campaigns, a new approach was used: the cervical smear was performed before the VIA test and, in case of a positive VIA test, the slide was sent for examination. The data collected were divided into two groups: the first six campaigns and the last three campaigns. Results: During the study period, 10 520 women were screened, of whom 911 had a positive VIA test. The VIA test showed 84.2% false positives. In the first group, the VIA test was positive in 516 women, of whom 93% were referred for further examinations. In the second group, the VIA test was positive in 395 women, but the cervical smear was positive in only 65 women. Thus, only 16.5% women were referred for further examinations. Conclusion: Combining cervical smear, VIA test, and slide analysis in positive VIA tests may allow women who need treatment to be selected more effectively, while waiting for other more expensive solutions to become more affordable for this setting. Abstract : Combining the cervical smear, VIA test, and slide analysis in positive VIA tests may be the most cost‐effective method for cervical cancer screening in Africa.